2021
DOI: 10.3390/biology10080769
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Host Genotype, Intestinal Sites and Probiotics Supplementation on the Gut Microbiota Composition and Diversity in Sheep

Abstract: Three sampling strategies with a 16s rRNA high-throughput sequencing and gene expression assay (by RT-PCR) were designed, to better understand the host and probiotics effect on gut microbiota in sheep. Sampling: (1) colon contents and back-fat tissues from small-tailed Han sheep (SHS), big-tailed Hulun Buir sheep (BHBS), and short-tailed Steppe sheep (SHBS) (n = 12, 14, 12); (2) jejunum, cecum and colon contents, and feces from Tan sheep (TS, n = 6); (3) feces from TS at 4 time points (nonfeeding, 30 and 60 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Through analysis, neither the jejunal nor colonic B/F value, ratio of phyla Bacteroidetes to Firmicutes, was directly correlated to the blood lipids in the experimental sheep, although their relative ratio has been used to demonstrate obesity effects in sheep and mice. 24,42 The divergence from their usual relationship in this study might be due to a shift in the effect of TA and GSPE, which diminished the concentration of blood lipids and which was more connected with altering the abundances of some critical bacteria genera. This result suggested that TA and GSPE have different influences on varied bacteria at various sites because of their different degradation along the digestive tract.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Through analysis, neither the jejunal nor colonic B/F value, ratio of phyla Bacteroidetes to Firmicutes, was directly correlated to the blood lipids in the experimental sheep, although their relative ratio has been used to demonstrate obesity effects in sheep and mice. 24,42 The divergence from their usual relationship in this study might be due to a shift in the effect of TA and GSPE, which diminished the concentration of blood lipids and which was more connected with altering the abundances of some critical bacteria genera. This result suggested that TA and GSPE have different influences on varied bacteria at various sites because of their different degradation along the digestive tract.…”
Section: Discussionmentioning
confidence: 67%
“…16S rRNA sequencing data were processed by QIIME1.9.1, USEARCH61, and UCLUST with 97% similarity, Ribosomal Database Project (RDP), and Greengenes (13_8 release) database to generate an OTU table, as we previously described. 24 Then the alpha diversity (Shannon diversity and Chao1 index) and beta diversity (weighted UniFrac distance) were calculated based on the above OTU table. While the functional potential of the gut microbiota community was analyzed by PICRUSt relying on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database.…”
Section: Microbiota Analysismentioning
confidence: 99%